Self-Fulfilling Debt Dilution: Maturity and Multiplicity in Debt Models - Aguiar, Mark; Amador, Manuel (American Economic Review, 2020)
We establish that creditor beliefs regarding future borrowing can be self-fulfilling, leading to multiple equilibria with markedly different debt accumulation patterns. We characterize such indeterminacy in the Eaton-Gersovitz sovereign debt model augmented with long maturity bonds. Two necessary conditions for the multiplicity are (i) the government is more impatient than foreign creditors, and (ii) there are deadweight losses from default. The multiplicity is dynamic and stems from the self-fulfilling beliefs of how future creditors will price bonds; long maturity bonds are therefore a crucial component of the multiplicity. We introduce a third party with deep pockets to discuss the policy implications of this source of multiplicity and identify the potentially perverse consequences of traditional “lender of last resort” policies. (JEL E44, E62, F34, H63, G12)